Peningkatan Keterampilan Merangkai Money Bouquet Melalui Video Tutorial pada Siswa Disabilitas Intelektual Ringan - Handayani, Riska Fitri; Iswari, Mega; Efrina, Elsa; Yuliana, Syari (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study was motivated by the difficulties experienced by an eighth-grade student with mild intellectual disability at SLB Negeri 1 Ampek Angkek in arranging a money bouquet. The purpose of this study was to improve money bouquet arrangement skills through the use of video tutorial media. The study employed a Single Subject Research (SSR) method with an A-B design. The participant was one student with mild intellectual disability. Data were collected through a performance test using a skill assessment instrument. Data analysis was conducted by comparing the results obtained during the baseline (A) and intervention (B) conditions. The findings indicated that during the baseline condition (A), the student's skill level was 42%, which was categorized as low. Following the intervention using video tutorial media in condition (B), the student's performance gradually increased to 57%, 66%, 71%, 90%, 90%, and 90%. Visual analysis revealed an increasing trend, high data stability, and an overlap percentage of 0%. Based on these findings, it can be concluded that video tutorial media was effective in improving the money bouquet arrangement skills of a student with mild intellectual disability at SLB Negeri 1 Ampek Angkek